2022
DOI: 10.1002/pc.26538
|View full text |Cite
|
Sign up to set email alerts
|

Influence of thermal deconsolidation on the anisotropic thermal conductivity of glass fiber reinforced, pre‐consolidated polypropylene sheets used for thermoforming applications

Abstract: Modeling how thermoplastic composites are processed using thermoforming is a challenging task, and not only due to the heterogenic nature of the material. During the thermoforming processes, the polymeric matrix has to be heated above the softening temperature, enabling the composite to be formed into three‐dimensional parts. As the system mobility increases, thermal deconsolidation takes place, and voids are created or expand within the composite sheet. These voids alter the sheet's material properties and ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…[14][15][16] In terms of genetics and other factors, studies found that gastric polyps occurrence and carcinogenesis connect mutations of tumor suppressor gene p53 and RAS, abnormal expression of tumor suppressor genes Ki67 and p16 and abnormal transduction pathways. [17][18][19] Logistic regression analysis showed that gender and age were also risk factors for gastric polyps. In addition, smoking and heavy drinking will increase the risk of gastric polyps, which may be related to smoking will increase the infection rate of HP, heavy drinking can cause gastric mucosal damage and other factors.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] In terms of genetics and other factors, studies found that gastric polyps occurrence and carcinogenesis connect mutations of tumor suppressor gene p53 and RAS, abnormal expression of tumor suppressor genes Ki67 and p16 and abnormal transduction pathways. [17][18][19] Logistic regression analysis showed that gender and age were also risk factors for gastric polyps. In addition, smoking and heavy drinking will increase the risk of gastric polyps, which may be related to smoking will increase the infection rate of HP, heavy drinking can cause gastric mucosal damage and other factors.…”
Section: Discussionmentioning
confidence: 99%
“…The oven and ambient experimental temperature curves were imported to HyperMesh and applied as convective thermal loads on the top and bottom surfaces of the simulated composite sample. The material properties of the composite components were estimated from literature values and personal communications with suppliers [16][17][18] . These values were then calibrated to better match the experimental temperature curves of the initial 120℃ test.…”
Section: Experiments Designmentioning
confidence: 99%